Poverty reduction programme in Georgia - Shatberashvili, Nino (Družboslovne razprave, 2014)
The article analyses the capability of the social assistance programme in Georgia to reach its goal and examines its potential to enable the targeted poor to meet their needs and improve their social functioning. The method used for presenting data includes a literature review, an analysis of reports and the use of the official statistics in the country. The main finding shows that the impact of the benefit varies across the population groups, with children remaining at the highest risk of poverty. Poverty rates vary across regions too, with mountainous regions being in the highest risk group. In June 2013, almost one-third of registered households in the database of socially unprotected families received a targeted Social Assistance Cash benefit. However, we can conclude that according to most benchmarks the programme has succeeded in terms of targeting disadvantaged groups, while as concerns the programme's efficiency and effectiveness there are areas for improvement regarding the coverage, the size and form of the benefit.
Keywords: Public welfare; Socialna pomoč; Revščina; Poverty; Georgia; Georgia (Republic); Gruzija; denarna socialna pomoč